2021
DOI: 10.21608/ejfsat.2021.54250.1182
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Evaluation of Piriform and Orbital Aperture in Sex Discrimination by Using Computed Tomography in Egyptian Population

Abstract: Human skeletal remains identification is crucial in forensic investigations, so the differentiation of the sex of a human bone is a significant initial stage for estimation of age and height of any unknown skeletal bone. AIM: The present study was designed to compare and evaluate the role of piriform and orbital aperture measurements in sex discrimination by using computed tomography in a sample of Egyptian population. SUBJECTS AND METHODS: This study was done by using 89 computed tomography (CT) images of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
5
1
0
Order By: Relevance
“…In Nitek et al (2009)'s study (1), it was noted that this parameter varies depending on the body side and is significantly larger on the left side (p˂0.05). Similarly to previous studies (9,10,13,16,19), it was found in our study that the height of the orbit was not affected by the body side. In our study, while the orbital height was similar to CT studies (13,14,17,19), it was found that it was larger than the results of dry bone and direct graphy studies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In Nitek et al (2009)'s study (1), it was noted that this parameter varies depending on the body side and is significantly larger on the left side (p˂0.05). Similarly to previous studies (9,10,13,16,19), it was found in our study that the height of the orbit was not affected by the body side. In our study, while the orbital height was similar to CT studies (13,14,17,19), it was found that it was larger than the results of dry bone and direct graphy studies.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly to previous studies (9,10,13,16,19), it was found in our study that the height of the orbit was not affected by the body side. In our study, while the orbital height was similar to CT studies (13,14,17,19), it was found that it was larger than the results of dry bone and direct graphy studies. The difference in the results of the study may be different methods, race and age groups.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Lidstone (2011) demonstrated, this will be achieved by attempting to identify male and female pattern of orbital shape using a series of landmarks along the margin of the orbits. In human, quantitative analysis aperture of orbit utilizing as a tool to identify sexes, had the greatest effect between observation and the revealed varying results (Sreekanth and Hema, 2019;El-Farouny, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%